Laser Monitor for Studying the Combustion of Thin Layers of Metal Nanopowders - Gubarev F. A. Fedor Aleksandrovich; Mostovshchikov A. V. Andrey Vladimirovich; Fedorov A. I. Anatoly Ignatjevich; Li Lin (2021, 2021)
Title screen